Employee Monitoring in the Digital Era: Managing the Impact of Innovation - Cliona McParland; Regina Connolly (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
The many obvious benefits that accompany digital technology have been matched by some less welcome and more contentious impacts. One of these is the steady erosion of privacy. For example monitoring and surveillance has become a fundamental part of the workplace environment, with employee performance often the main object of scrutiny. With companies now competing within a rapidly changing global economy, managers are forced to satisfy market trends that are driven by productivity and efficiency. Attempts to satisfy these imperatives have resulted in a relentless drive to improve performance and increase efficiency. In fact, the increasing number of organisations that monitor employees through advanced digital technologies has added a dystopian edge to existing employee privacy concerns, particularly as many employees are unable to exercise choice in relation to use of these technologies. If unaddressed, their concerns have potential to impact the psychological contract between employee and employer, resulting in loss of employee trust, negative attitudes and counterproductive work behaviours. This paper outlines some of the emerging issues relating to use of employee monitoring technologies. It summarises both management rationale for monitoring as well as employee privacy concerns in an effort to balance the perspectives of both parties.
Keywords: O33; 330; privacy; monitoring; trust; surveillance; empowerment; workplace; behaviours